Prasangka Dalam Prespektif Al- Qur’an Kajian Tahlili Qs. Al-Hujarat Ayat 12 - Rian; Muhammad Hisyam Hisyam; Taufan (Rahmad : Jurnal Studi Islam dan Ilmu Al-Qur'an, 2025)
This study aims to provide guidance to avoid prejudice against society. In QS. Al-Hujarat 49/12 This type of research is qualitative with a form of library research. The approach used is the interpretation approach. The data used are primary data sourced from the Qur'an and interpretation books and secondary data including related works and other references that can support the research, then processed and analyzed using the tahlili method. The results of the study indicate that the nature of 'Prejudice in QS. Al-Hujarat 49/12 is all forms of prejudice carried out by humans, where the act contains hatred and hostility, is considered reprehensible and causes evil, so that the perpetrators are far from the truth and mercy of Allah swt. And also good prejudice where this prejudice actually brings you closer to Allah swt. because it always looks at others well, the form of 'Prejudice in QS. Al-Hujarat 49/12, namely accusing people without evidence and looking at the bad things in others and some of these suspicions are also good.